S-Layer From Lactobacillus brevis Modulates Antigen-Presenting Cell Functions via the Mincle-Syk-Card9 Axis - Prado Acosta, Mariano; Goyette-Desjardins, Guillaume; Scheffel, Jörg; Dudeck, Anne; Ruland, Jürgen; Lepenies, Bernd (Frontiers in Immunology, 2021)
C-type lectin receptors (CLRs) are pattern recognition receptors that are crucial in the innate immune response. The gastrointestinal tract contributes significantly to the maintenance of immune homeostasis; it is the shelter for billions of microorganisms including many genera of Lactobacillus sp. Previously, it was shown that host-CLR interactions with gut microbiota play a crucial role in this context. The Macrophage-inducible C-type lectin (Mincle) is a Syk-coupled CLR that contributes to sensing of mucosa-associated commensals. In this study, we identified Mincle as a receptor for the Surface (S)-layer of the probiotic bacteria Lactobacillus brevis modulating GM-CSF bone marrow-derived cells (BMDCs) functions. We found that the S-layer/Mincle interaction led to a balanced cytokine response in BMDCs by triggering the release of both, pro- and anti-inflammatory cytokines. In contrast, BMDCs derived from Mincle-/-, CARD9-/- or conditional Syk-/- mice failed to maintain this balance, thus leading to an increased production of the pro-inflammatory cytokines TNF and IL-6, whereas the levels of the anti-inflammatory cytokines IL-10 and TGF-β were markedly decreased. Importantly, this was accompanied by an altered CD4+ T cell priming capacity of Mincle-/- BMDCs resulting in an increased CD4+ T cell IFN-γ production upon stimulation with L. brevis S-layer. Our results contribute to the understanding of how commensal bacteria regulate antigen-presenting cell (APC) functions and highlight the importance of the Mincle/Syk/Card9 axis in APCs as a key factor in host-microbiota interactions.